The effects of seasonality, landscape variables and anthropogenic activities in structuring bird community in Dutse, Nigeria / Sulaiman Inuwa Muhammad - Sulaiman Inuwa, Muhammad (2018)
Seasonality and landscape transformations due to human activities are threatening global biodiversity, especially in Africa where most conservation effort seems feeble, coupled with paucity of data. Several studies on birds have been conducted in Nigeria but none had been conducted in Dutse, Northwestern Nigeria. This study aims to reveal the relationships between ecological parameters and diversity as well as abundance of birds in relation to seasonality, landscape variables and anthropogenic activities. The presence of birds in four sites (Warwade, Malamawa, Model and Wangara) was recorded via direct observation technique from August 2015 to February 2016. Data were collected over the period of wet and dry seasons and across woodland and shrubland habitats. All sites were dominated by woodland habitat except for Wangara (a shrubland habitat). Using the point transect method, 264 points on 48 km of transect were used to count birds between 0630 – 1100 hours. A total of 128 bird species (13,656 individuals) from 46 families were recorded, with Accipitridae having the highest bird species. The vulnerable Beaudouin's Snake Eagle (Circaetus beaudouini) and the near threatened Pallid Harrier (Circus macrourus) were also recorded. Highest bird species richness was recorded in Warwade, while highest abundance and diversity was recorded in Model. Dry season and woodland habitat showed higher bird species richness, abundance and diversity. Tree density was more important in increasing bird abundance than shrub density. The most abundant feeding guild was insectivores (48%), followed by granivores (16%) and frugivores (16%). Frugivore abundance was significantly higher in woodland habitat and the Model site. Majority of bird species in Dutse were residents (72%) while few species are non-breeding visitors (main range) (10%), residents (partially migratory) (8%), non-breeding visitors (sparse occurrence) (6%), or breeding visitors (4%). The woodland and shrubland habitats had higher proportion of resident and migratory species. Similarly, Model and Wangara sites had higher proportion of resident and migrant birds respectively. Population trend assessments by the IUCN Red List of Threatened Species suggested that 57% of bird species in the study area showed stable population trend while 20% showed decreasing, 18% increasing and 5% uncertain trends. The dry season recorded higher abundance of insectivores, granivores and frugivores, residents and migrants, and birds with increasing, decreasing and stable population trends than the wet season. Both woodland and shrubland in Dutse are vital as bird habitats but migrant species utilized shrubland habitat more than woodland. Small-scale anthropogenic activities and habitat modification (such as farming, grazing, wood removal and human interference) did not appear to have affected the birds. However, loss of high tree density in woodland habitat may pose a major threat to the bird community in Dutse. High numbers of both resident and migrant bird species highlight the importance of Dutse as a key habitat and wintering ground in the region. Similarly, the presence of birds of concern in the area suggest the need for conservation efforts of avifauna and as well as the forested habitats in Dutse.